Delovnopravno varstvo žvižgačev (whistleblowing) - Senčur Peček, Darja (Delavci in delodajalci, 2015)
The paper deals with the issues related to labour law protection of a worker or public servant who in good faith reports illegal, corruptive or harmful conduct of the employer whereby it also presents the international framework of this protection, some solutions in other legal systems, and the legal regulation of this field in Slovenia.
Keywords: delodajalci; delovno pravo; javni uslužbenci; kazniva dejanja; odpoved; pogodba o zaposlitvi; pravno varstvo; prekrški; prenehanje; zaposleni